Application of PET/CT in Preoperative Evaluation and Diagnosis of Gastric Cancer. (4th April 2022) - Zhou, Xin; Zhang, Yongpeng; Zhao, Xipeng; Zhou, Lin; Jia, Xia; Pan, Libo
Abstract : The aim study to study the significance of pet clinical examination image technology for early gastric mucosal adenocarcinoma, improve the accuracy and accuracy of image examination results of gastric cancer, and provide important reference significance and value for early treatment. Study methods, we used the experimental method of clinical medicine to obtain some reference data through the intervention of different image examinations on experimental patients of different groups and stages, These data show that the use of PET-CT imaging can improve the one-year survival rate of patients and reduce the one-year recurrence rate. Lymphatic metastasis rate and hematogenous metastasis rate, so as to highlight the advantages of PET-CT imaging.